Pre-crystallization process in chocolate: Mechanism, importance and novel aspects - Pirouzian, Haniyeh Rasouli; Konar, Nevzat; Palabiyik, Ibrahim; Oba, Sirin; Toker, Omer Said (ELSEVIER SCI LTD, 2020)
Pre-crystallization is an important step in the production of chocolate, which is defined as tempering of cocoa butter through primary and secondary nucleation. The goal of tempering is to obtain a sufficient amount of beta(v) polymorph of the right size. The pre-crystallization process has a great impact on the quality and production cost of final product. Development of chocolate technology requires the use of the most appropriate techniques and ingredients without negatively affecting the quality characteristics. Applications of novel technologies within the confectionery industry have allowed production of chocolate in sufficient quantities to meet the public needs. In order to provide and investigate the potential and usage of novel technologies, the present review focused on different pre-crystallization methods and factors affecting the processing conditions. Seeding and ultrasound-assisted pre-crystallization can be used as alternatives to conventional tempering process. However, in both methods, optimization of experimental conditions is required.
Keywords: Chocolate; Pre-crystallization; Tempering; Seeding; HIGH-INTENSITY ULTRASOUND; COCOA BUTTER; CRYSTALLIZATION BEHAVIOR; DARK CHOCOLATE; IN-SITU; POLYMORPHIC TRANSFORMATION; SORBITAN MONOSTEARATE; FUNCTIONAL-PROPERTIES; PHYSICAL-PROPERTIES; FREEZING PROCESSES; Chemistry; Food Science & Technology; Nutrition & Dietetics